Tokyo as a leading global financial center: The vision under the spotlight again - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2017)
Japan has endeavored to develop its capital Tokyo as one of the top global financial centers for a long time. In 2014, the Tokyo Metropolitan Government presented new initiatives as part of the sustainable economic growth strategies by taking advantage of the global attention given to the 2020 Tokyo Olympic Games. Japan's advantages are the sheer size of its economy (the third largest in terms of gross domestic product); the status of the Japanese yen as the third international currency after the United States dollar and the euro; and large financial and capital markets with abundant capital. Tokyo has the potential to become a regional financial center that transfers excess capital to emerging Asia given its geographic proximity. So far, this vision has not fully materialized because Japan's financial investment continues to be destined toward the United States and Europe and in the form of relatively safe debt securities. Moreover, Japan's capital remains largely risk averse, contributing to lack of diversity in domestic capital markets and limited provision of risk money to the world. This paper takes an overview of Japan's financial and capital market developments.
Keywords: E4; F21; G21; 330; global financial center; international portfolio investment; Exchange-Traded Funds (EFT); Real Estate Investment Trust (REIT)